O Paternalismo nas organizações brasileiras: reflexões à luz da análise cultural de empresas do pólo têxtil de americana - Moreira, Carlos Augusto Amaral (2005)
This thesis tries to discuss the present times of the paternalism as a cultural trait of the Brazilian organizations. Recovering the Brazilian cultural roots and being supported by established anthropological, sociological and psychoanalytical papers, it establishes a central hypothesis that the paternalism can be found nowadays, in Brazil, not only in small companies, where the paternal control is predominant, but also in bigger and more complex companies, with a tendency towards the development of a maternal control system, where the paternalism would give rise to a Brazilian control version. Ethnographic field research, made in three distinct extent companies from the Textile Pole of Americana-SP, showed favorable signs for the central hypothesis, presenting, however, important peculiarities which, the same way as give permission to refine it, it also indicates tracks for new studies. At the smaller and less complex company, the paternalism was shown in its most known way, in the practices either affectionate or severe of the company’s directors. At more complex companies, we could note the expression of the parents’ action that regulates their sons’ joy. The protective and the violent side are revealed in the moment that the mother’s love access is given or restricted. In the three studied cases, the paternalism appears with its warm side significantly predominant in relation to the violent side, what it seems to be an element associated with the success experienced by such companies.